Niche partitioning at emergence of two sympatric top-predator dragonflies, Anax imperator and A. parthenope (Odonata: Aeshnidae). Issue 1 (2nd January 2018) - Boucenna, Nedjwa; Kahalerras, Amin; Boukhemza-Zemmouri, Nabila; Houhamdi, Moussa; Khelifa, Rassim
Summary: In natural communities, closely related species are phenotypically similar but usually spatially and/or temporally isolated. In odonates, interspecific competition occurs not only at the larval or adult stage but also during emergence. We investigated the emergence of two sympatric Anax species, focusing on the temporal pattern, vertical stratification, and body size trend over time. Anax imperator started to emerge two weeks earlier than A. parthenope but most of the emergence season overlapped. Both species showed an asynchronous emergence and the median emergence date was 10.3 days earlier in A. imperator . Sex ratio at emergence was not significantly different from 1:1. Body size of both species increased significantly over time, which contrasts many previous studies. The height of exuvia fixation was not significantly different between species but the larger species A. parthenope selected longer supports.